Synthesis and gelation assessment of functionalized diphenylalanine dipeptides : towards cell culture applications - Heiskanen, Noora (2023)
The literature part of this master’s thesis discusses the usage of hydrogels in cell culture. It goes through the microenvironmental aspects that need to be considered when choosing a hydrogel for cell culture. The differences between natural, synthetic and hybrid hydrogels are explained, and examples of hydrogels used in biomedical applications are described. The aim of the experimental part was to synthesise 9-fluorenylmethyloxycarbonyl-protected diphenylalanine dipeptide (FmocFFCOOH) and cinnamoyl-protected diphenylalanine dipeptide (CinFFCOOH) to compare their gelation properties. The nuclear magnetic resonance (NMR) spectroscopic, high-resolution mass spectrometric (HR-MS) and Fourier-transform infrared (FT-IR) spectroscopic analyses were performed to identify the products and prove their purities. For FmocFFCOOH, the conducted gelation trials showed promising results. Unfortunately, for CinFFCOOH, there was not enough clean product or time to do gelation analysis